Síntese e aplicação de pirazóis na construção de poliheterociclos com potencial bioatividade - Moraes, Paulo Alexandre de (2022)
This work reports the synthesis of eight series of substituted trifluoromethyl heterocycle compounds, based on the synthetic versatility and regioselectivity of 4- alkoxy(amino)-5-bromo-1,1,1-trifluorpent-3-en-2-ones in reactions of Nfunctionalization using nitrogenous nucleophiles. Many of the compounds obtained have interesting physical and chemical characteristics from a pharmacological point of view, since they are analogous to synthetic drugs well known on the market and which have varied biological activities. The series of precursors, compounds (E)-4-(amino)1,1,1-trifluor-5-(5-methyl-3- (trifluormethyl)-1H-pyrazoles-1-yl)pent-3-en-2-ones (pyrazole-enaminones), was synthesized through the N-alkylation reaction via bimolecular nucleophilic substitution (SN2), where the bromine atom at position five (Cγ) of the bromo-enaminones, was replaced by the nucleophilic nitrogen of the pyrazoline ring, promoting the formation of N-alkylated products with yields ranging from 65 and 86%. From this precursor unit, cyclocondensation reactions were carried out using different dinucleophiles, exploring their synthetic versatility as building blocks and thus obtaining the other series of polyheterocycle compounds of this work that had yields between 20 and 98%. Using bispyrazoles as a platform, a controlled and regioselective synthetic route was developed containing consecutive steps of N-alkylation and cyclocondensation for the synthesis of novel polypyrazoles composed of pyrazoline monomers along along the main chain with yields between 35 and 96%. This methodology was also adapted for the construction of the necessary molecular structure that will serve as a basis for future ring-closing reactions in the synthesis of macrocycles. The products obtained were characterized by 1H and 13C NMR, mass spectrometry, high resolution mass spectrometry, elemental analysis and by x-ray diffraction.